The incidence, characteristics, and complications of pregnant women who delivered stillbirths under different child policies in central China - Xiong, Lili; Xie, Donghua; Jiang, Qingyun; Fang, Junqun (Frontiers in Public Health, 2025)
BackgroundChina’s evolving fertility policies (one-child to three-child) have shaped maternal and neonatal outcomes, but specific gaps in stillbirth epidemiology during policy transitions.MethodsThis retrospective cohort study analyzed 721,860 singleton pregnancies in 2011–2023, from 18 maternal near-miss surveillance hospitals in Hunan. Stillbirth rates were assessed across four policy periods: one-child (2011–2013), partial two-child (2013–2015), universal two-child (2016–2020), and three-child (2021–2023). Multivariable logistic regression identified risk factors, adjusting for fertility policy period, maternal demographics and maternal comorbidities. Trends over time were analyzed using segmented regression models.ResultsThe overall stillbirth rate was 7.02‰ (95% confidence interval [CI]: 6.82–7.21), declining significantly from 9.62‰ during the one-child policy to 5.73‰ (95%CI: 5.25–6.23) under the three-child policy (t = −4.22, p < 0.01). Key risk factors included maternal age < 24 years (adjusted odds ratio [aOR] = 1.77, 95%CI:1.63–1.92), multiparity (aOR = 1.27–2.82. p < 0.01), non-rural hospital delivery (aOR = 4.00–11.13, p < 0.01), education ≤9 years (aOR = 1.51–2.20, p < 0.01), not being married (aOR = 2.92–5.60, p < 0.01), and comorbidities: severe preeclampsia (aOR = 3.80, 95%CI: 3.36–4.29), chronic hypertension (aOR = 2.67, 95%CI: 2.09–3.37), placental abruption (aOR = 5.06, 95%CI: 4.11–6.16), and placenta previa (aOR = 1.55, 95%CI: 1.29–1.84). Paradoxically, prenatal diabetes was associated with reduced stillbirth risk (aOR = 0.86, 95%CI: 0.77–0.95). Temporal shifts revealed elevated stillbirth rates among advanced-age mothers pre-2016 versus rising rates in women <24 years post-policy liberalization. Only the partial two-child policy period (aOR = 1.15, 95%CI: 1.05–1.25) was associated with the risk of stillbirth.ConclusionChina’s fertility policy transitions correlate with dynamic stillbirth epidemiology, emphasizing age- and parity-specific vulnerabilities. Targeted interventions for high-risk subgroups, especially younger, less well-educated, multiparous women, and those with hypertensive or placental disorders, are critical amid ongoing implementation of the three-child policy.